THE RELATIONSHIP BETWEEN STUDENTS' SOCIAL-PSYCHOLOGICAL ADAPTATION AND PSYCHOLOGICAL SAFETY (Universal International Scientific Journal, 2026)
this article presents a theoretical and empirical analysis of the interrelationshipbetween students’ socio-psychological adaptation and their psychological safety within theeducational environment. Socio-psychological adaptation is defined as the student's ability tointegrate into the school environment, adjust to teacher expectations, and maintain socialrelationships with peers. Psychological safety is conceptualized as the student’s internal feeling ofemotional stability, social acceptance, and security in school. The article substantiates that bothconstructs are mutually reinforcing and must be addressed together to ensure holistic studentdevelopment. Pedagogical and psychological strategies such as psychological climate monitoring,differentiated instruction, social support mechanisms, and school psychological services aresuggested as effective solutions
Keywords: psychological safety; socio-psychological adaptation; safety in the educational environment